Factors Associated with the Occurrence of Vaginal Discharge in Female Students - Suminar, Erni Ratna; Sari, Vianty Mutya; Magasida, Diani; Agustiani, Ati Rohayati (Program Studi Kebidanan Fakultas Kedokteran Universitas Sebelas Maret, 2022)
Introduction: A teenager begins to experience psychological changes and developments such as changes in mindset and emotional stability. Teenager is prone to complaints of Vaginal charge. Vaginal charge inurement from the vaginal and it is not blood discharge nor menstrual blood, vaginal charge becomes a Leucorrhoea when the discharge becomes smelly and local itching. The cause of vaginal discharge can be normally influenced by hormones. There are factors influence the incidence of vaginal discharge in adolescents, including knowledge, media information, personal hygiene, viruses, bacteria and parasites and others.Methods: This study uses quantitative research methods with a cross sectional approach with female respondents at SMAN 7 Cirebon City. The population in this study were all female students at SMAN 7 Cirebon City. The sampling technique used total sampling. It is including female students in SMAN 7 Cirebon City with a total of 587 people.Result: The majority of the characteristics of students' knowledge about the occurrence of vaginal discharge with good knowledge were 262 respondents (93.2%), media information on the incidence of vaginal discharge through electronic media were 492 respondents (96.7%) and personal hygiene on the incidence of vaginal discharge by not doing personal hygiene were 394 respondents (98.7%).Discussion: There is a significant relationship between knowledge (p-0.031, information media (p-0.003), and personal hygiene (p-0.000) on the incidence of vaginal discharge in female students of SMAN 7 Cirebon City with p<0.05.